Dampak Pembangunan PLTU Terhadap Perubahan Sosial Masyarakat di Desa Lampoko Kecamatan Balusu Kabupaten Barru: Dampak Pembangunan PLTU terhadap Masyarakat: Studi Kasus Perubahan Sosial di Lampoko Kabupaten Barru - fitriani; Sulvinajayanti; M. Rifqi Miftahun Nurulhad (IAIN Parepare, 2023)
The existence of the PLTU in Lampoko Village, Barru Regency, has an impact on changes in society, these changes occur in the people who live around the PLTU. This research aims to determine the forms of social change brought about by the presence of the PLTU construction and the impact of this development on the social life of the community. This research used a qualitative descriptive method, with the aim of describing in more detail the impact of PLTU construction on social change in society. The theories used in this research are rational choice theory and modernization theory. Data collection techniques were carried out by means of observation, interviews and documentation with data analysis techniques using data reduction, data presentation and drawing conclusions. The results of this research show that the presence of the PLTU construction in the Lampoko Village area has an influence on the social life of the community, the form of influence that is generated in the community, namely changes in social behavior, in this case the decline in friendly behavior among fellow citizens in the community and changes in the community's mindset, this can seen in the mindset of society in the fields of entrepreneurship and education. Beside that, the presence of this development also has an impact on the social life of the residents of Lampoko Village. The positive impact of the presence of the PLTU construction in the Lampoko Village area is improving the community's economy, opening up new job opportunities, CSR social services, and changing the profession of residents from fishermen/farmers to PLTU employees. Meanwhile, the negative impacts resulting from the presence of the PLTU include pollution of the social environment and unequal absorption of local labor.